2006
DOI: 10.3892/ijmm.17.5.899
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of liver fibrogenesis by dual inhibition of PDGF and TGF-β with a combination of imatinib mesylate and ACE inhibitor in rats

Abstract: Abstract. Both platelet-derived growth factor (PDGF) and transforming growth factor-ß (TGF-ß) are known to be pivotal cytokines in liver fibrosis development. The aim of our current study was to elucidate the effects of dual inhibition of PDGF and TGF-ß by combination of the clinically used imatinib mesylate (STI-571) and perindopril (an ACEinhibitor; ACE-I), respectively, on ongoing liver fibrosis development in rats. The effects of STI-571 and ACE-I at clinically comparable low doses were examined in a rat m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
(54 reference statements)
2
29
0
Order By: Relevance
“…These results are in agreement with the previous study of Yoshiji et al (2005), which demonstrated the prophylactic potential of imatinib to produce a significant hepatic fibrosis reduction via suppression of activated HSCs during 8 weeks of concomitant stimulation with pig serum. Combination treatment of imatinib and ACE-I inhibitor, perindopril, significantly attenuated liver fibrosis development (Yoshiji et al 2006). Also, it has been reported that daily IP injection of imatinib caused a marked decrease of proliferation in isolated HSCs in an experimental model of rats with 48 h of acute bile duct ligation liver injury (Kinnman et al 2001).…”
Section: Discussionmentioning
confidence: 98%
“…These results are in agreement with the previous study of Yoshiji et al (2005), which demonstrated the prophylactic potential of imatinib to produce a significant hepatic fibrosis reduction via suppression of activated HSCs during 8 weeks of concomitant stimulation with pig serum. Combination treatment of imatinib and ACE-I inhibitor, perindopril, significantly attenuated liver fibrosis development (Yoshiji et al 2006). Also, it has been reported that daily IP injection of imatinib caused a marked decrease of proliferation in isolated HSCs in an experimental model of rats with 48 h of acute bile duct ligation liver injury (Kinnman et al 2001).…”
Section: Discussionmentioning
confidence: 98%
“…Lastly, but more importantly, since other growth factors (PDGF, IGF, epidermal growth factor, HFG as shown in fig. 4 ) can quite effectively signal via RTK by activating several molecules shared by TGF-Smad-independent pathways in certain cell types, it is not unusual for TGF-␤ to share its role with other growth factors in EMT in development [Yamane et al, 2003;Karihaloo et al, 2005;Mukherjee et al, 2005;Gwon, 2006;Yoshiji et al, 2006].…”
Section: Activation Of Tgf-␤ Receptormentioning
confidence: 99%
“…Antifibrotic effects of imatinib have also been reported in other organ systems such as the liver (Yoshiji et al, 2006) and kidney (Wang et al, 2005). Daniels et al (2004) studied the effects of imatinib in female 129tsvems mice subjected to intratracheal bleomycin; imatinib at 50 mg/kg/day administered on day 1 after bleomycin injury for a period of 28 days mediated significant protection from fibrosis.…”
mentioning
confidence: 99%